(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
Uniquely preserved and diverse ostracod faunas from Middle Triassic (Ladinian) beds of the Balaton Highland (Hungary) are described and figured. The preservation is due to silicification of fine texture of the carapaces and valves providing high quality data for taxonomical analyses. The benthic faunas from three localities (Litér, Felsőörs and Nemesvámos) consist of 28 taxa belonging to 12 genera. Four species are new: Polycope arcuatocosta n. sp., P. densoreticulata n. sp., Ptychobairdia tenuiornata n. sp. and Praemacrocypris literense n. sp. Based on morphological and ecological characteristics the studied benthic ostracod assemblages are the latest occurrences of the Thuringian-type assemblages sensu Becker. The dominance of the Thuringian-type elements, smooth bairdiaceans and metacopids indicates an open marine, more than 200 m deep, oligotrophic, bathyal environment with low energy conditions.